Sweeney Todd the demon barber of Fleet Street - Sondheim, Stephen; Hughes, Terry (Terry W.); Prince, Harold, 1928-; Lansbury, Angela, 1925-; Hearn, George; Bond, C. G. (Christopher Godfrey), 1945-; Wheeler, Hugh, 1912- (Burbank, CA : Warner Home Video, 2004)
Returning to London after his wrongful imprisonment, a barber seeking revenge provides a local baker with fresh meat for her meat pies.
Based on the play by Christopher Bond, which was based on the novel by Hugh Wheeler.
Angela Lansbury, George Hearn.
Not rated.
DVD, Dolby digital 5.1 surround.
In English with optional English, French, or Spanish subtitles.
Closed-captioned.
Keywords: Bond, C. G. -- 1945- -- Film and video adaptations; Wheeler, Hugh, -- 1912- -- Film and video adaptations; Todd, Sweeney (Legendary character) -- Drama; Revenge -- Drama; Musicals; Film and video adaptations